2001
DOI: 10.4401/ag-3603
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation creep model of impending earthquake

Abstract: The alternative view of the current status and perspective of seismic prediction studies is discussed. In the problem of ascertainment of the uncertainty relation Cognoscibility-Unpredictability of Earthquakes, priorities of works on short-term earthquake prediction are defined due to the advantage that the final stage of nucleation of earthquake is characterized by a substantial activation of the process while its strain rate increases by the orders of magnitude and considerably increased signal-to-noise rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…(i) The launch of the preseismic MHz radiation systematically precedes the kHz one (Gokhberg et al, 1995;Matsumoto et al, 1998;Hayakawa Fujinawa, 1994;Hayakawa, 1999;Morgounov, 2001;Kapiris et al, 2004;Eftaxias et al, 2002, and references therein). This situation is also observed at the laboratory scale by means of AE and EME.…”
Section: A Three-stage Model For Earthquake Generation By Means Of Pr...mentioning
confidence: 99%
See 3 more Smart Citations
“…(i) The launch of the preseismic MHz radiation systematically precedes the kHz one (Gokhberg et al, 1995;Matsumoto et al, 1998;Hayakawa Fujinawa, 1994;Hayakawa, 1999;Morgounov, 2001;Kapiris et al, 2004;Eftaxias et al, 2002, and references therein). This situation is also observed at the laboratory scale by means of AE and EME.…”
Section: A Three-stage Model For Earthquake Generation By Means Of Pr...mentioning
confidence: 99%
“…However, recent accumulated experimental evidence enhanced some older ones indicating that the aforementioned well accepted view was false; the recorded AE and EME, in general, are not two sides of the same coin. Indeed, simultaneous laboratory measurements of AE and EME reveal the existence of two categories of AE signals (Yamada et al, 1989;Mori et al, 1994;Morgounov, 2001;Mori et al, 2004aMori et al, , b, 2006Mori et al, , 2009Mori and Obata, 2008;Lacidogna et al 2010;Baddari and Frolov, 2010;Carpinteri et al, 2012) As it was mentioned, laboratory studies reveal that strong AE and EME are simultaneously observed during stress drops occurred close to peak stage in the load versus time diagram (Fukui et al, 2005;Lacidogna et al, 2011;Carpinteri et al, 2011;Carpinteri et al, 2012). At this stage new fresh surfaces, which are accompanied by the rupture of interatomic bonds and charge separation, are produced.…”
Section: An Approach By Means Of Laboratory Experiments and Numerical...mentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of finite-time-singularity in the anomalies strongly supports the hypothesis of presence of a positive feedback mechanism, which expresses a positive circular causality that acts as a growth-generating phenomenon and therefore drives unstable patterns (Telesca and Lasaponara, 2006). The appearance of the property of irreversibility in a probable precursor is one of the important components of predictive capability (Morgounov, 2001).…”
Section: Introductionmentioning
confidence: 99%